2013
DOI: 10.5455/2319-2003.ijbcp20131007
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on prevalence of adverse drug reactions due to antibiotics usage in otolaryngology department of a tertiary care hospital in North India

Abstract: Background: Polypharmacy, advancing age and longer duration of hospital stay are the factors responsible for adverse drug reactions (ADRs). This study has attempted to analyze the pattern of antimicrobial prescription in OPD & IPD of the Otolaryngology department and to detect, document, assess and report the suspected ADRs due to antibiotic use and preparation of guidelines to minimize the incidence of ADRs. Methods: A prospective study conducted at the TMMC&RC on patients aged >40 years, who visited the Otol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 14 publications
(22 reference statements)
3
11
1
7
Order By: Relevance
“…Following the previous studies by Mahatme and Narasimharao, Gupta et al, and Jung et al, the present study showed the predominance of cutaneous manifestations on presentation of ADRs (75%) [13][14][15] followed by central nervous system manifestations such as dizziness. However, several other studies have observed gastrointestinal symptoms such as vomiting and diarrhea as the most common manifestation of ADR [16][17][18]. The drug dechallenge was done in most of the cases and in some, the dose was reduced while no changes were made in others considering the risk-benefit ratio in particular patients.…”
Section: James and Ranimentioning
confidence: 99%
“…Following the previous studies by Mahatme and Narasimharao, Gupta et al, and Jung et al, the present study showed the predominance of cutaneous manifestations on presentation of ADRs (75%) [13][14][15] followed by central nervous system manifestations such as dizziness. However, several other studies have observed gastrointestinal symptoms such as vomiting and diarrhea as the most common manifestation of ADR [16][17][18]. The drug dechallenge was done in most of the cases and in some, the dose was reduced while no changes were made in others considering the risk-benefit ratio in particular patients.…”
Section: James and Ranimentioning
confidence: 99%
“…[9] Studies revealed that ADRs are leading to hospitalization and constitute a significant economic burden on patients in India. [101112] A study showed that hospital admissions due to ADRs accounted for 0.7% of total admissions and deaths due to ADRs accounted for 1.8% of total admissions in a territory referral center in South India. [13]…”
mentioning
confidence: 99%
“…3 Studies revealed that ADRs are leading to hospitalization and constitute a significant economic burden on patients in India. [4][5][6] WHO defines "adverse reactions as harmful and unintended responses to a drug and which occur with doses normally used in humans for prophylaxis, diagnosis or treatment of a disease or modifying a physiological function". 7 Studies conducted in several parts of India have estimated the incidence of suspected adverse reactions to be nearly 2% to 3% among hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%